A simple, low cost, three dimensional model for teaching regional angiology and neurology - CHANDRASEKHAR, LEENA; RAVINDRAN, REGHU; RAJA, T V; CHUNGATH, JOSE JOHN (The Indian Journal of Animal Sciences, 2013)
This paper describes a simple and low cost method for teaching veterinary angiology and neurology. The aim is to improve the quality of anatomical education through a student centred and clinically oriented approach. The acceptance of this method of teaching was surveyed among students. The results suggested that the model is well received by students.